(untitled) (Water Nepal, 2003)
Safe drinking water is essential to life, but for many millions of people, safe water is a dream. The report of the WHAT Water Commission draws attention to the tragedy that more than one billion people in the world lack access to safe drinking water and that annually, something of the order of four million people die prematurely from water-borne diseases. It quotes an United Nations Environment Programme statement that ‘The world water cycle seems unlikely to be able to cope with the demands that will be made on it in the coming decades. Severe water shortages already hamper development in many parts of the world.’ Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.29-36